(untitled) (Research, Society and Development, 2024)
Objective: To describe the structural and functional alterations of the stomatognathic system, and to identify and disseminate information about speech therapy in facial trauma caused by violence against women. Methodology: A survey of articles was carried out in three databases: Virtual Health Library (VHL), Public Medicine Library (PubMed) and Scientific Electronic Library Online (SciELO), after which descriptors were established in Portuguese and English. After this process, the inclusion and exclusion criteria that guided the search were defined. Initially, 41 articles were identified in the databases. After surveying the literature and applying the exclusion criteria, 14 articles were selected. Of these, after thorough analysis, 10 met the inclusion criteria for this review. Results: Of the 10 articles included, structural alterations were found, such as facial disfigurement, nasal fractures, fractures of the orbit, maxilla, mandible, zygomatic complex, soft tissue injuries, dento-alveolar trauma, craniofacial injuries, panfacial fractures, ecchymosis and abrasions in the cervical and frontal regions, which consequently compromise the functions of the stomatognathic system. Conclusion: This study described the main structural alterations: facial disfigurement, nasal fractures, mandible, maxilla and zygomatic complex, which affect the functions of the stomatognathic system, such as breathing, phonation, chewing and swallowing. There are no reports of damage to suction. This study has highlighted and identified the importance of speech therapy based on the myofunctional approach to facial trauma.